Reconstruction of Charismatic Leadership Model in Islamic Education Based on Religious Moderation at Ash-Shiddiqiyah Serpong Islamic Boarding School - Muhammad Rio Zarkasyi Aziz; Hasyim Asya’ari; Sita Ratnaningsih (Universitas Negeri Jakarta, 2025)
This study aims to reconstruct the charismatic leadership model in Islamic education based on religious moderation at Ash-Shiddiqiyah Serpong Islamic Boarding School. The research employs a descriptive qualitative approach with field study methods, collecting data through in-depth interviews, participatory observation, and documentation involving pesantren leaders, teachers, senior students, and organizational managers. Data analysis follows the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings reveal three primary dimensions of reconstructed charismatic leadership: (1) moderate prophetic charisma integrating tolerance and national values, (2) value-based transformative leadership fostering collective change through moral exemplarity, and (3) adaptive educational governance accommodating diversity through curriculum flexibility and external collaboration. The study demonstrates that charismatic leadership in pesantren can be institutionalized beyond personal authority by embedding moderation principles into managerial systems and organizational culture. These findings contribute to contemporary Islamic leadership theory by proposing an integrative framework that harmonizes spiritual charisma with modern governance and religious moderation, offering a replicable model for Islamic boarding schools navigating pluralism and globalization.